Algorithm and simulation of heat conduction process for design of a thin multilayer technical device. (5th February 2016) - Ayriyan, Alexander; Buša, Ján; Donets, Eugeny E.; Grigorian, Hovik; Pribiš, Ján
Highlights: The cryogenic cell realizes thermal gate valves for the millisecond pulse injection. The developed algorithm gives stable solution for fast oscillating of source. The temperature regime in the cell has two stages: setting mode and working mode. The optimal choice of cell characteristics provides the required pulsing regime. Abstract: A model of a multilayer device with non-trivial geometrical structure and nonlinear dependencies of thermodynamic material properties at cryogenic temperatures is suggested. A considered device, called cryogenic cell, is intended for use in multicharged ion sources for pulse injection of gaseous species into ionization space of ion sources. The main requirement for the cryogenic cell operation is the permanent opening and closing for gaseous species injection in a millisecond range, while cell closing is provided by freezing of the gaseous specie at the outer surface of the cell and the cell opening – by the corresponding pulse heating of the cell surface up to definite temperature. The thermal behavior of the device in a millisecond time range is simulated. The algorithm for solving the non-stationary heat conduction problem with a time-dependent periodical heating source is suggested. The algorithm is based on finite difference explicit–implicit method. The OpenCL realization of the algorithm is discussed. The optimal particular choice of the parameters to provide the required pulse temperature regime of the designed cryogenic cell for the chosen working gas is presented. Based on these results further optimization can be formulated.